Synthesis and characterization of titanium-based metallic glass biocomposite film for surface modification of 316L stainless steel implant - Bidabad, Mohsen Saraf (2012)
This work is a study to show applicability of a new class of amorphous metallic material that are called metallic glass (MG) or glassy metal in biomedical application as a biofilm. Superior properties of these alloys designate them as a new age of biomaterial in biomedical applications, but thickness limitation in bulk form is the main problem for their production. Presented idea in this study intends to fabricate and implement them in composite thin film form for surface modification of a biomedical grade of stainless steel (316L) with weak surface properties that is widely applied as bone implant. This type of coating can solve production constraints of MG materials to be implemented in wide range of biomedical or other industrial applications. For depositing these alloys, PLAD technique was used as a versatile technique to make amorphous film so that stoichiometry and other excellent properties were preserved in deposited film and related source in PLAD target. PLAD vacuum chamber was designed according to the research requirements. The target was composed of two parts. First is a Ti-based MG matrix obtained in Ti-Cu-Zr-Si system by mechanical alloying and second is tricalcium phosphate (TCP), which is a bioceramic phase for improving film biocompatibility and osseointegration. Before deposition and sample making, laser-target interaction was simulated by COMSOL Multiphysics computer software to predict cooling rate and maximum temperature in irradiated zone on surface target. Relationship between them and process parameters was estimated and the optimum amount of process parameters was predicted. Regarding to simulation results, PLAD was done to deposit MG composite films on 316L SS. Finally, physical characteristics of synthesized as deposited films were evaluated and biological assays in vitro and in vivo were performed for selected samples successfully. Performed biological results confirmed that connectivity between as-deposited TCP/Ti-based MG composite film and osteoblast like cells (MG63) was desirable and cytotoxicity in presence of these films was in low level in contrast with uncoated 316L SS. The composite films with 15 wt.%, TCP additive in Ti40Cu30Zr5Si25 MG matrix were the best composition both in physical and biological film characteristics. According to the predicted PLAD process parameters and practical experiments based on them, obtained results had a particular agreement with our hypothesis. Based on physical and structural properties it was found that by using a Gaussian Nd:YAG pulsed laser at second harmonic wavelength equivalent to 532nm and pulse duration about 140 ns, a Ti-based MG thin film is deposited on heated 316L SS successfully. Numerical calculations indicate that cooling rate in irradiated zone reaches to about 106 K/s as atoms have no chance to order in crystalline structure and have to form an amorphous structure. Film characterization techniques such as XRD and DSC confirm this and show full amorphicity in as-deposited film structure when process parameters including vacuum pressure, target rotation speed and substrate temperature set at 10-5 Torr, 2000 rpm, (450-500 ) respectively as predicted in the modeling. It reveals that experimental results are in good agreement with the modeling and it is proven that PLAD is capable to form a thin MG film on metallic substrate as was desirable in hypothesis. Both performed surface characterization (topography, morphology, hardness and wettability) and short-term biocompatibility assay (MTS, hemolytic and acute systemic toxicity) for coated and uncoated 316L SS samples illustrated that coated samples with this synthesized composite film were enhanced significantly in comparison with uncoated 316L SS and these new synthesized films meet essential requirements for an implant coating in biomedical applications.